Penggunaan Alat Peraga Pola Bilangan Pada Pembelajaran Matematika Di SMP Negeri Mainang - Loban, Jeni Marianti; Maryanes Astriani Malese; Narita Yuri Adrianingsih; Landerius Maro (Pusat Riset dan Inovasi Nasional, 2023)
Visual aids are tools that can stimulate students' thoughts, skills, attention and willingness so that they can encourage the learning process in students, besides that using teaching aids can provide space for students to be actively involved in every learning process. In fact, in Toyang State Junior High School, mathematics learning has not used visual aids. The props created and used are number pattern boxes made of used cardboard, which are designed in such an attractive way to form several number pattern boxes consisting of: square, rectangular and triangular boxes. This visual aid is used in the learning process for class VIII students of SMP Negeri Toyang. This training aims to help foster the creativity of students and improve students' ability to use teaching aids. The result of this training is that students get new experiences by learning to use visual aids, this can be seen from the enthusiasm of the students who are very large and students more easily understand the concept of number patterns